Towards Content Adaptation For Mobile Learning - Ran, Yang Shu (2010)
The study develops the content adaptation of m-learning. M-learning content adaptation is quite important, combining mobile technologies and learning together are highly valued by researchers. Content adaptation refers to different kinds of software and coding applications that use for learning. In order to develop mobile content adaptation, we should follow some principles for mobile devices features and learning characteristics.